Pengembangan Tongkat Cerdas Pemandu Tunanetra Menggunakan Arduino Berbasis Sensor Ultrasonik - Joni Eka Candra (AI Society & STMIK Indonesia, 2025)
This research aims to develop a smart cane that can be used as a guide for the blind by utilizing Arduino technology and ultrasonic sensors. This smart cane is designed to help blind people detect and avoid obstacles around them, thereby increasing safety and independence when walking. The method used in this research involves designing and manufacturing hardware and software that are integrated into a smart stick. Ultrasonic sensors are used to detect the distance and presence of objects in front of the user, while the Arduino microcontroller processes the sensor data and provides feedback in the form of vibrations or warning sounds. Trials were carried out on several blind people to evaluate the effectiveness and practicality of this tool. The research results show that this Arduino-based smart stick with an ultrasonic sensor is able to detect objects with good accuracy and provide quite effective warnings to users. The feedback provided allows users to recognize and avoid obstacles more easily, thereby increasing confidence when moving in unfamiliar environments. Thus, it is hoped that this smart cane can be an innovative and practical solution to increase the mobility and independence of blind people. This research also opens up opportunities for further development in assistive technology for people with disabilities.